Costs and Effects of Left Atrial Venous Drainage Cannula Placement in Veno-Arterial ExtraCorporeal Membrane Oxygenation (LAVA ECMO) via Transeptal Puncture for Left Heart Decompression – A Single Institution Case Series (Global Journal of Medical Research, 2023)
Background Peripherally cannulated patients on veno-arterial extra corporeal membrane oxygenation support may require left heart venting to offload the left ventricle and allow for myocardial rest and recovery Which venting strategy is optimal is currently not known Methods We performed a retrospective single-institution case series of fifteen patients who underwent left atrial venous drainage veno-arterial ECMO The venous drainage cannula was a multistage single venous drainage cannula that was placed with fluoroscopic and echocardiographic guidance across the inter-atrial septum The primary outcome of interest was six-month survival Secondary outcomes included echocardiographic indices of left ventricular distention platelet and bilirubin trend post cannulation survival on ECMO and surgical outcome
Keywords: ECMO; cardiogenic shock; myocardial recovery